Immune Checkpoint Inhibitors: Cardiotoxicity in Pre-clinical Models and Clinical Studies - Xu, Shirley; Sharma, Umesh C.; Tuttle, Cheyanna; Pokharel, Saraswati (Frontiers in Cardiovascular Medicine, 2021)
Since the approval of the first immune checkpoint inhibitor (ICI) nine years ago, ICI-therapy have revolutionized cancer treatment. Lately, antibodies blocking the interaction of programmed death receptor (PD-1) and ligand (PD-L1) are gaining momentum as a cancer treatment, with multiple agents and cancer types being recently approved for treatment by the US Food and Drug Administration (FDA). Unfortunately, immunotherapy often leads to a wide range of immune related adverse events (IRAEs), including several severe cardiac effects and most notably myocarditis. While increased attention has been drawn to these side effects, including publication of multiple clinical observational data, the underlying mechanisms are unknown. In the event of IRAEs, the most widely utilized clinical solution is administration of high dose corticosteroids and in severe cases, discontinuation of these immune checkpoint inhibitors (ICIs). This is detrimental as these therapies are often the last line of treatment options for many types of advanced cancer. In this review, we have systematically described the pathophysiology of the PD-1/PD-L1 axis (including a historical perspective) and cardiac effects in pre-clinical models, clinical trials, autoimmune mechanisms, and immunotherapy in combination with other cancer treatments. We have also reviewed the current challenges in the diagnosis of cardiac events and future directions in the field. In conclusion, this review will delve into this expanding field of cancer immunotherapy and the emerging adverse effects that should be quickly detected and prevented.